Analysis Green of Accounting Practice Implementation: Study on Sea Product Exporting Companies in Gorontalo City - Husain, Siti Pratiwi; Noholo, Sahmin; Polapa, Melisa Putri Sinto; Salzabila, Shabrina (Universitas Negeri Gorontalo, 2025)
Purpose: The application of green accounting by companies is a form of corporate responsibility towards society and the environment, where companies care about the environment as a result of the company's operational activities. This research aims to determine whether business owners know and implement green accounting practices.Design/Methodology/Approach: This research method uses a qualitative descriptive approach guided by case studies—data collection techniques through observation, interviews, and documentation of research objects.Findings: The results of this research regarding understanding and concern in implementing Green Accounting at CV. Berkat Adidaya Gorontalo has implemented Green Accounting by not throwing away factory products carelessly but instead sorting and filtering waste before disposal. By implementing green accounting, companies try to reduce environmental pollution by paying attention to the waste produced due to company activities.